2022
DOI: 10.1063/5.0076298
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a gas bubble penetrating through porous media

Abstract: Porous media have been widely used for liquid-gas separation, benefiting from the strong capillary force generated from the micro/nanoscale pores. Understanding the flow characteristics in pore scale is significant for the design of porous structure. In this study, a numerical model was established to investigate the dynamics of a bubble penetrating through porous media at the pore scale. The two-phase interface was captured using the diffuse interface method. The influence of pore shape, width, and height on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…While studies on continuum scale can provide a lot of useful information, the behavior of bubbles cannot be directly observed. A few studies reported the effect of fundamental variables on air bubble transport in porous media using computational models or microfluidic devices [16][17][18]. For instance, some studies demonstrated the mechanisms of foam generation in microchannels [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…While studies on continuum scale can provide a lot of useful information, the behavior of bubbles cannot be directly observed. A few studies reported the effect of fundamental variables on air bubble transport in porous media using computational models or microfluidic devices [16][17][18]. For instance, some studies demonstrated the mechanisms of foam generation in microchannels [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have comprehensively studied the former three mechanisms Mogro-Campero, 1978, 1979;Saunders et al, 1999), the basic principles and controlling parameters for bubbly flow from deep ground formations to the ground surface, proposed by Etiope and Martinelli (2002), have not been comprehensively investigated and developed. This research objective is, so far, still at an initial stage with a few academic attempts (Ma, 2015;Mahabadi et al, 2018;Chang and Lindquist, 2020;Yi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%